Motivación y el desempeño laboral de los servidores administrativos de la Gerencia Sub Regional Ucayali Contamana 2025 - Pezo Shapiama, Carlos Daniel (2025)
The objective of the study was to determine the relationship between motivation and job performance of the administrative servants of the Ucayali Sub Regional Management Contamana 2025. It was a research of basic nature, with descriptive-correlational character and a non-experimental design. The study population consisted of 75 administrative servers. The results revealed that 23% of the participants presented a medium level of motivation. This perception was due because on occasion servers strove to achieve challenging goals and felt incentivized in the face of the proposal of new work challenges. In a similar way, 27% of the assessed servers showed an average job performance, as they claimed to complete their tasks within the set deadlines and without affecting the quality of their work. However, the majority manifested that they almost always tried to carry out their activities in an efficient manner and sought to continuously improve their performance. Finally, it was determined that there is a positive and statistically significant relationship between job motivation and job performance, evidenced by a Spearman coefficient of 0.682 and a significance level of 0.000, lower than the threshold of 0.01. Similarly, a coefficient of 0.672 is evident for achievement motivation, 0.677 for affiliation motivation and 0.350 for power motivation. These results confirm that all dimensions of job motivation are significantly related to the performance of administrative servers.